2003
DOI: 10.1089/089277903767923146
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience in Laparoscopic Partial Nephrectomy for Renal Tumor with Clamping of Renal Vessels

Abstract: The technique of LPN can be standardized and should be proposed for small tumors when they are not invading the hilum. Clamping the renal pedicle allows better vision for more accurate tumor excision with a safety margin and hemostatic suturing of the parenchymal defect, resulting in less blood loss and shorter operative time, parameters that improve with experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Nephron-sparing surgery is an effective and reliable treatment in low stage renal tumors [1] . Clamping the renal pedicle allows better visualization, helping accurate tumor excision and hemostatic suturing of the parenchymal defect [2] , however it entails renal ischemia and sometimes leads to ischemic injury when it is prolonged. In previous studies measuring serum creatinine, Bhayani et al [3] showed that warm ischemic time up to 55 min did not significantly influence longterm renal function after LPN.…”
Section: Introductionmentioning
confidence: 99%
“…Nephron-sparing surgery is an effective and reliable treatment in low stage renal tumors [1] . Clamping the renal pedicle allows better visualization, helping accurate tumor excision and hemostatic suturing of the parenchymal defect [2] , however it entails renal ischemia and sometimes leads to ischemic injury when it is prolonged. In previous studies measuring serum creatinine, Bhayani et al [3] showed that warm ischemic time up to 55 min did not significantly influence longterm renal function after LPN.…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical scenarios exist where information like that obtained in this work has potential impact. The transplant and laparoscopic literature report that there is a lack of knowledge regarding the vascular pedicle and renal ostium relative to the aorta, which may potentially affect laparoscopic renal transplant surgery and laparoscopic nephrectomies (Bermudez et al, 2003). CTA has been shown to be useful in the assessment of prospective living renal donors (Rydberg et al, 2001;Fleischmann, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The orientation of the renal vascular pedicle is important for laparoscopic urologic procedures like donor nephrectomy (Bermudez et al, 2003). The right pedicle has *42.98 anteromedial orientation with a three-degree difference resulting in more anterior orientation for women.…”
Section: Discussionmentioning
confidence: 99%
“…Lower set: Conventional suturing with tangential transmission of force which can result in 'cheese cutting' effect and has its own risks [9]. Infusion of a cold solution at 4°C delivered via a ureteral catheter could also be used [10], but the efficacy of this has not been extensively tested.…”
Section: Cold Ischemiamentioning
confidence: 99%